Challenge athletes to improve their self-worth: A serial mediation model linking dual controlling behaviors to sport performance. (September 2021) - Cheng, Yu-Hung; Chou, Wan-Ju; Kao, San-Fu; Chou, Te-Hsien
Abstract: Coaches can shape athletes' self-worth through controlling behaviors, such as tight control and stressful challenge. However, previous research has not paid attention to the effects of different controlling behaviors of coaches on athletes' self-worth, which is considered an important motive for athletes to achieve high performance. Accordingly, the dual controlling model of leadership behaviors is adopted to clarify the effects of controlling behaviors. Also, sociometer theory is adopted to investigate the mechanism by which controlling behaviors influence athletes' self-worth and their sport performance. Data were collected from 16 male college basketball teams in Taiwan, from a total of 155 participants. Results show that different controlling behaviors have opposite effects on sport performance, and these effects are mediated serially by coach–athlete relationship quality (i.e., leader–member exchange) and self-worth (i.e., team-based self-esteem). This study contributes to the literature of coaching by examining and identifying the opposite effects and the black box of dual controlling behaviors on athletes' performance. Highlights: Controlling behaviors can be divided into tight control and stressful challenge that affect athletes' performance oppositely. Adopting sociometer theory, LMX and TBSE serially mediate the effects of dual controlling behaviors on athletes' performance. Coaches should maintain athletes' LMX and TBSE through providing stressful challenges.